Local Wisdom of Osing People in Conserving Water Resources - Sumarmi, Sumarmi (KOMUNITAS: International Journal of Indonesian Society and Culture, 2015)
Each tribe in Indonesia has certain local wisdom to conserve their environment, including managing water resources. The purpose of this research is to identify the local wisdom of Osing people in conserving water resources in Kemiren, Glagah Sub-District, Banyuwangi. This research uses descriptive qualitative method. The data are taken through interview, observation and documentation. The local wisdom of Osing people in managing water resources involves knowledge, values, moral and ethics, and norms, which are applied in forms of suggestions, rules and sanctions, and also old sayings as a guideline for them to behave and act in maintaining, keeping and conserving Mbah Buyut Citi water spring. To keep a constant flow of water debit, they protect trees and plants around the spring (belik), both belik lanang and belik wadon. In maintaining this local culture, the older generations pass on the values, moral, ethics, and norms including Islamic norms (most of them are Moslem) as the guidelines on how to behave and act in practicing the traditions and instincts for respecting the environment to their family, neighbours, relatives and children-grandchildren.Masing-masing suku di Indonesia memiliki kearifan lokal tertentu untuk melestarikan lingkungan mereka, termasuk kearifan untuk mengelola sumber daya air. Tujuan dari penelitian ini adalah untuk mengidentifikasi kearifan lokal masyarakat Osing dalam melestarikan sumber daya air di Kemiren, Kecamatan Glagah, Banyuwangi. Penelitian ini menggunakan metode deskriptif kualitatif. Data diambil melalui wawancara, observasi dan dokumentasi. Kearifan lokal masyarakat Osing dalam mengelola sumber daya air meliputi pengetahuan, nilai-nilai, moral dan etika, dan norma-norma yang diterapkan dalam bentuk saran, aturan dan sanksi, serta kata-kata bijak sebagai pedoman bagi mereka untuk bersikap dan bertindak dalam menjaga, menjaga dan melestarikan mata air Mbah Buyut Citi. Untuk menjaga aliran konstan debit air, mereka melindungi pohon-pohon dan tanaman di sekitar musim semi (belik), baik belik lanang dan wadon belik. Dalam mempertahankan budaya lokal ini, generasi tua mewariskan nilai-nilai, moral, etika, dan norma-norma termasuk norma-norma Islam (kebanyakan dari mereka adalah Muslim) sebagai pedoman tentang bagaimana bersikap dan bertindak dalam menjalankan tradisi dan naluri untuk menghormati lingkungan untuk keluarga mereka, tetangga, kerabat dan anak-cucu.